Pentraxin 3 and other inflammatory biomarkers related to atrial fibrillation in cardiac surgery - Holubcova, Zdenka; Kunes, Pavel; Mandak, Jiri; Vlaskova, Dana; Kolackova, Martina; Holmannova, Drahomira; Andrys, Ctirad; Krejsek, Jan; Holubec, Tomas (Perfusion, 2017)
OBJECTIVES: The aim was to evaluate the association between perioperative inflammatory biomarkers and atrial fibrillation (AF) in cardiac surgical patients. METHODS: Forty-two patients undergoing cardiac surgery were divided into three groups according to the occurrence of AF: Group A (n = 22) - patients with no AF, Group B (n = 11) - patients with new onset AF postoperatively and Group C (n = 9) - patients with preoperative history of atrial fibrillation. The serum levels of PTX3, CRP, TLR2, IL-8, IL-18, sFas, MMP-7 and MMP-8 were measured at the following time points: before surgery, immediately and 6 h after surgery and on the 1st, 3rd and 7th postoperative days (POD). RESULTS: Serum levels of PTX3 showed a significant difference between Groups A and C on the 3rd POD (p<0.05) and on the 7th POD (p<0.0001). IL-8 levels were different between Groups A and C immediately after surgery (p<0.05), 6 hours after surgery (p<0.05) and on the 3rd POD (p<0.05). There was a difference between Groups B and C on the 1st POD in IL-8 levels (p<0.05). The sFas levels differed between Groups A and C on the 3rd POD (p<0.01) and the 7th POD (p<0.05). There was also a difference on the 7th POD (p<0.05) between the Groups B and C. No significant differences between the groups was seen for other biomarkers. CONCLUSION: This study demonstrates significantly different dynamics of PTX3, IL-8 and sFas levels after cardiac surgery in relation to AF.
Keywords: kardiochirurgické výkony; Humans; biomarker; atrial fibrillation; lidé středního věku; C-reaktivní protein; Female; Aged; inflammation; senioři; lidé; Atrial Fibrillation; Biomarkers; pentraxin 3; Serum Amyloid P-Component; Cardiac Surgical Procedures; biologické markery; ženské pohlaví; Male; Middle Aged; sérový amyloidový protein; cardiac surgery; mužské pohlaví; C-Reactive Protein; fibrilace síní